The Influence of Independency, Professionalism, and Integrity on Fraud Prevention with Leadership Style As Moderating Variable - Yunita Sari; Helmi Yazid; Muhammad Taqi (Journal of Applied Business, Taxation and Economics Research, 2022)
This research aims to analyze the influence of independence, professionalism, and integrity against fraud prevention with leadership style as moderating variable. This research uses a survey method with a questionnaire instrument to collect data. Data collection in this research was carried out by distributing questionnaires to respondents directly. The results of this research indicate that First, independence has a significant positive effect on fraud prevention. Second, professionalism has a significant negative effect on fraud prevention. Third, integrity has a significant positive effect on fraud prevention. Forth, leadership style not moderate the influence of independence on fraud prevention. Fifth, leadership style can moderate the influence of professionalism on fraud prevention. Sixth, leadership style not moderate the influence of integrity on fraud prevention.